Description of a new diminutive Hyloxalus (Anura: Dendrobatidae: Hyloxalinae) from the Magdalena Valley of Colombia - Acosta-Galvis, Andrés R.; Vargas-Ramírez, Mario; Anganoy-Criollo, Marvin; Ibarra, Oscar A.; Gonzáles, Sandra (Zootaxa, 2020)
Using different sources of evidence (i.e., integrative taxonomy), we describe a new species of Hyloxalus, Hyloxalus arliensis sp. nov. The new species occurs in the middle Magdalena River valley on slopes between the Cordillera Central and Cordillera Oriental of the Andes of Colombia. Previously, the new species was referred to as Hyloxalus “Ibagué” but was not formally described. Phylogenetic re-analyses of 2440 base pairs (bp) of mitochondrial DNA (mtDNA), revealed the species to be a sister taxon of H. lehmanni, within a monophyletic clade also comprising H. delatorreae lineage 1, H. pulchellus and H. vertebralis. The adult males of H. arliensis sp. nov. have a pale arm gland, which differentiates it from all other species of the genus, except for H. saltarius. The new species also differs from other species of Hyloxalus by its smaller size, disc on Finger III not expanded, toes unwebbed, dorsolateral stripe absent, oblique lateral stripe present, white spots on ventrolateral flanks in life and cloacal tubercles absent. The advertisement call consists of long trains of a single note repeated at a rate of 89–132 notes/min with a dominant frequency ranging from 4808–6387 Hz. The new species is a tiny frog that inhabits the sheltered areas around streams in sub-Andean forests. Aspects of its natural history are described.